RESILIENSI SPIRITUAL PASCABENCANA - Ataupah, Noviyan Kefinabu; Harisantoso, Imanuel Teguh; Adi, Suwarto (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This study explores the impact of a landslide disaster on the spiritual life of the Evangelical Christian Church in Timor (GMIT) Victory Noelmina congregation, which consists of members from Noelmina Village and its surrounding areas. The research focuses on the effects of the disaster on the congregation's spirituality, including the intensity of worship, involvement in church ministry, and spiritual resilience in facing trauma and loss. This study employs a qualitative method with a single case study approach. The research subjects are three families from the GMIT Victory Noelmina congregation directly affected by the disaster, selected through purposive sampling. Data collection techniques include in-depth interviews, participatory observation, and documentation, while data analysis was conducted thematically through data reduction, presentation, and conclusion drawing. The findings indicate that the landslide disaster increased the congregation's spirituality. Worship attendance rose from 60% to 91%, and participation in church ministries such as prayer meetings and catechetical worship increased. Spiritual resilience became a key factor in trauma recovery, where the congregation interpreted the disaster as an opportunity to strengthen their relationship with God and others. In conclusion, the disaster brought negative impacts and catalyzed spiritual growth and community solidarity, relevant to Christian theology in addressing life's challenges.